The Mediating Role of Managing the High Involvement Management Between Organizational Power and Negotiation StrategiesAnalytical Research of the Views of a Sample of Leaders of the Iraqi Ministry of Industry and Minerals - Neamah, Hassan Abdulkareem; Mhaibes, Hussam Ali (Journal of Economics and Administrative Sciences, 2021)
The research aims to test the relationship and impact of High Involvement Management as an independent variable in negotiation strategies as a response variable, at the headquarters of the Iraqi Ministry of Industry and Minerals in Baghdad Governorate, and then trying to come up with a set of recommendations that contribute to strengthening the negotiations carried out by the ministry’s leaders and based on the importance of the topic of research in public organizations and the importance of the surveyed organizations to the society. The descriptive-analytical approach was adopted in the completion of this research, and the research included a sample of (180) leaders of the Iraqi Ministry of Industry and Minerals, and data was collected from (120) respondents who represent the research community exclusively and comprehensively, represented by (general managers, directors of departments people managers). By adopting the questionnaire, which included (47) paragraphs, the personal interviews were used during the distribution of the questionnaire and the explanation and clarification of its paragraphs. The research adopted the program Amos V.26, Spss V.26) with the adoption of descriptive statistics methods (linearity test, normal distribution test, confirmatory factor analysis, building models of variables, arithmetic mean, percentages, standard deviation, relative importance, and coefficient of variation, Pearson correlation coefficient, simple regression coefficient, path analysis, Sobel test) to test its hypotheses. As for the most prominent conclusions of the research that showed the validity of the hypotheses, they were embodied in the effect of high inclusion directly in the negotiation process and its strategies, and from it, we conclude that the management of high inclusion affects the negotiation directly and indirectly, and on this basis, these indirect influences contributed to increasing the value of the effect. The research came out with a number of recommendations; the most important of which is the investment of the reciprocal and interactive relationship between the management of high containment and negotiation strategies, directly or indirectly, with the realization that their elements and dimensions and their ability to develop, change and add in a way that coincides with the development and diversity of jobs and changes in the accelerating environment